EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KOPI, KAKAO, DAN JAMBU METE DI KECAMATAN MORAMO UTARA KABUPATEN KONAWE SELATAN - -, M. TUFAILA; -, ALIYAMAN; GINTING, SAHTA; ALAM, SYAMSU (Jurnal Agroteknos, 2014)
This study aimed to determine the level of land suitability for cultivation of coffee, cocoa and cashew on the Experimental Farm of Halu Oleo University in the District of North Moramo, South Konawe. The method used in this research was the method of soil survey aimed to obtain data on soil characteristics. Land suitability evaluation was done by using the method of matching between the land characteristics and the eligibility criteria to grow crops that will be developed. Results on actual land suitability for coffee crop was quite suitable (S2) with a land area of 149.6 ha, marginally suitable (S3) with total area of 101.06 ha and not suitable (N) with 3.01 ha land area; whereas for cocoa and cashew plants was marginally suitable (S3) with total area of 246.21 ha and not suitable (N) with 7.46 ha land area. Potentially, coffee plants were quite suitable (S2) with a land area of 213.65 ha, marginally suitable (S3) with a land area of 37.01 ha and not suitable (N) with 3.01 ha land area; cocoa plants were marginally suitable (S3) with a land area of 250.76 ha and not suitable (N) with 3.01 ha land area while cashew plants were quite suitable (S2) with a land area of 246.21 ha, marginally suitable (S3) with 4.45 ha land area and not suitable (N) with 3.01 ha land area. Factors limiting plant growth were rainfall, air temperature, air humidity, soil depth, slope and erosion. Management action carried out for the limiting factors erosion and slope was by land conservation, for the limiting factor of rainfall was by irrigation system settings and no management actions coul be done for the limiting factors of air temperature, humidity and soil depth because the limiting factors are permanent.